Atherogenic Indices in cases of idiopathic preterm premature rupture of membranes and healthy pregnant controls: A Comparative Study - Kirubalenin, Shanmuga Priya (2025)
Objective: To evaluate and compare atherogenic indices in women with idiopathic Preterm Premature Rupture of Membranes (pPROM) and gestational age matched healthy pregnant controls. Material and methods: In the Departments of Biochemistry and Obstetrics & Gynecology at UCMS & GTBH-Delhi, a cross-sectional comparative pilot study was carried out from August 2023 to July 2024. The study comprised 60 participants: 30 women with idiopathic pPROM (26-34 weeks gestation) and 30 controls with uncomplicated pregnancies who were matched for gestational age. We computed the following atherogenic indices: non-HDL-C, Lipoprotein Combined Index (LCI), LDL-C/HDL-C, TC/HDL-C, Atherogenic Coefficient (AC) and Atherogenic Index of Plasma (AIP) and analysed the data. Results: HDL-C levels were lower in idiopathic pPROM group. TC, TG, and LDL-C levels were higher in cases of idiopathic pPROM group. CRP levels were also higher in cases of idiopathic pPROM group, indicating increased systemic inflammation. All atherogenic indices except non-HDL-C were significantly elevated in the idiopathic pPROM group. Conclusion: Compared to healthy pregnant age-matched controls, women with idiopathic pPROM had a significantly pro-atherogenic lipid profile, elevated atherogenic indices and a higher inflammatory milieu. These findings also suggest a potential mechanism that links dyslipidaemia with proinflammatory state with membrane weakening, and ultimately resulting in premature rupture of membranes. Thus, these women require closer monitoring for timely interventions to alleviate adverse outcomes.